Role of Technology in Marketing: AI, AR and VR - Zahid Hussain; Muhammad Zain Shaikh (CV. Ulil Albab Corp, 2023)
Artificial intelligence, augmented reality, and Virtual reality have fundamentally transformed customer-brand relationships. These technologies have the potential to allow companies to customize their product or service, and messages to their target audiences the specific preferences and needs. These emerging technologies have gotten a lot of attention in the marketing world as a new way to attract customers and improve their brand experiences. The goal of this study is to identify the most important aspects of AI, AR, and VR for the successful adoption of business in the marketing sector. This research work is aimed to analyze the impact of AI, AR, and VR on marketing.